Bacharel, tecnólogo e agora professor: a constituição da docência na educação profissional - Lins, Antonio Blanco Acioli (2022)
Throughout history, Professional Education (PE) has not been on the agenda of effective policies for teacher training of professionals who work in this type of education, which has professionals with varied educational profiles who work as teachers there, often without having undergone pedagogical training. Thus, in this research, we sought to answer the following problem: How does the constitution of professional education teachers take place, having as reference the multiple dimensions of teaching knowledge? We aimed to analyze the constitution (formation, insertion in teaching, constituted knowledge, recognition as a teacher) of the teaching of non-licensed professionals who work in BS. As a theoretical basis to support this research we rely on authors who deal with the knowledge of teaching, such as Tardif (2012), Gauthier (2013), Pimenta (2012), and professional education, such as Kuenzer (2012), Machado (2008), Moura (2008) and others. The methodological path followed the assumptions of the qualitative approach with inspiration in the methodology of action research, having as institutional context the Center for Technological Education of Amazonas-CETAM. The research participants were 07 non-licensed professionals who work as teachers in technical professional education medium level, which responded to semi structured interviews organized according to a previous script of questions, transcribed and analyzed following the prerogatives of the spiral analysis proposed by Cresweel (2014). From the reports of the participating teachers, it was possible to learn that they entered the teaching profession due to lack of opportunities in the specific area and to supplement their salaries. Experiential knowledge is predominant in their practices, with emphasis on the models provided by former teachers and the specific knowledge built throughout their work activities. There were also reports about the difficulties derived from the deficiency of pedagogical knowledge. These results are consistent with the literature and reflect the lack of specific training to work in professional education, which historically, has always occurred through emergency actions and improvisation. Moreover, the research participants did not demonstrate clarity about teaching as a profession, considering here their theoretical and procedural knowledge. Considering the results of this research and the fact that it is articulated to a professional master's degree, we built, as an educational product, a Didactic Guide entitled "I am an PE teacher: what should I do? Expanding the knowledge for teaching in Vocational Education", aiming to contribute to the construction and expansion of teaching knowledge, especially the theoretical foundations of vocational education and pedagogical knowledge. Besides the didactic guide, a website (www.antoniolins.com) is produced composed of videos that discuss the guiding concepts of professional education, as well as concepts and terms related to pedagogical knowledge. The teachers considered the Didactic Guide, the Website, and the course to be very good in terms of design, language, objectives, and target audience, and considered it to be a pedagogical material of great value for the teaching work in PE. As future perspectives and taking into account the current context of political changes in teacher education, we understand that more reflection and discussions are need to address the specificity of the training profile for teaching in BS, aiming at the realization of an omnilateral training that can articulate work, science, technology and culture.